Construction of the Offender in Child Sexual Abuse Prevention Training for Adults. Issue 4 (2nd October 2017) - Nurse, Anne M.
Abstract : Until recently, the media was Americans' primary source of information about child sexual offenders. Today, however, millions of adults attend child sexual abuse prevention trainings sponsored by churches, schools, and other organizations. This paper draws on participant observation in 22 sessions of a popular Catholic program. It examines how the curriculum frames child sexual offenders and how group processes support or challenge that framing. While such trainings have the potential to challenge incorrect stereotypes, group and organizational pressures often coalesce to perpetuate fear, anger, and an inability to see offenders as anything but "others."